Physical Activity in School Children in a Pandemic Period?: A Systematic Review - Gilang Ramadan (JUARA : Jurnal Olahraga, 2022)
The purpose of this study was to review articles that were carried out systematically and qualitatively synthesized on physical activity for school students during a pandemic. The research method carried out by conducting a limited search was on studies published in the article search period from 2019 to 2021 by following the PRISMA guidelines, the search was carried out by systematically identifying 135 publications that underwent title, abstract, or full-text review. Studies were excluded if the articles were not in English or did not include original data. The results of a systematic review found 14 articles that met the eligibility criteria, based on self-reported data as many as 60% to 70% of school students did not meet the recommendations for physical activity that should be done such as walking, playing sports and cycling. Intrinsic factors such as motivation, the goal of maintaining health and changes in body shape provide a significant factor for the physical activity carried out. In conclusion, many factors cause this, such as the social environment, home environment, and changes in hormones, which are factors that often occur due to low physical activity. Physical activity that is often done but in low intensity is walking, cycling and sometimes doing the treadmill. Given that physical activity is not just physical activity outside the home, it is far from being a health promotion tool for a long period.